The echo manual - Oh, Jae K.; Seward, J. B. (James B.); Tajik, A. Jamil (Philadelphia : Lippincott Williams and Wilkins, 2007)
Thoroughly updated for its Third Edition, this manual is a practical guide to the performance, interpretation, and clinical applications of echocardiography. The Echo Manual is written by recognized authorities at the Mayo Clinic and provides a concise, user-friendly summary of techniques, diagnostic criteria, and quantitative methods for both echocardiography and Doppler echocardiography. Discussion of each clinical problem also includes transesophageal echocardiography. This edition covers the latest techniques, standards, and applications and includes new contrast agents. All references have been updated. More than 900 images--well annotated and true to gray scale and color--give readers an immediate grasp of salient points.
How to obtain a good echocardiography examination: ultrasound physics, technique, and medical knowledge -- Transthoracic echocardiography: M-mode, two-dimensional, and three-dimensional -- Transesophageal and intracardiac echocardiography / Jae K. Oh [and others] -- Doppler echocardiography and color flow imaging: comprehensive noninvasive hemodynamic assessment -- Tissue doppler imaging, strain imaging, and dyssynchrony assessment / Brian D. Powell [and others] -- Contrast echocardiography -- Assessment of systolic function and quantification of cardiac chambers -- Assessment of diastolic function and diastolic heart failure -- Pulmonary hypertension and pulmonary vein stenosis -- Coronary artery disease and acute myocardial infarction -- Stress echocardiography -- Valvular heart disease -- Prosthetic valve evaluation -- Infective endocarditis -- Cardiomyopathies -- Cardiac diseases due to systemic illness, genetics, medication, or infection -- Pericardial diseases -- Tumors and masses -- Diseases of the aorta -- Echocardiography in congenital heart disease: an overview / Frank Cetta, Jr., James B. Seward, Patrick W. O'Leary -- Intraoperative echocardiography / Roger L. Click, Jae K. Oh -- Vascular imaging and tonometry / A. Rauoof Malik, Iftikhar J. Kullo -- Goal-directed and comprehensive examination.
Includes bibliographical references and index.
Keywords: Echocardiography -- Handbooks, manuals, etc; Echocardiography -- methods